Parkinson's disease severity and motor subtype influence physical capacity components - Pereira, Marcelo Pinto [UNESP]; Silva Pelicioni, Paulo Henrique [UNESP]; Bucken Gobbi, Lilian Teresa [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2013)
The severity of Parkinson's disease (PD) and PD's motor subtypes influence the components of physical capacity. The aim of this study was to investigate the impact of both PD severity and motor subtype in the performance of these components. Thirty-six PD patients were assigned into four groups: Tremor (TD) initial and TD mild, akinetic-rigid (AR) initial, and AR mild. Patients' strength, balance, coordination, mobility and aerobic capacity were evaluated and groups were compared using a two-way ANOVA (severity and subtype as factors). AR presents a poorer performance than TD in almost all tests. Also this performance was worsened with the advance of the disease in AR, contrary to TD. We conclude that AR and TD subgroups are different about their performance on physical capacity components, moreover, this performance worsens with the advance of the disease of the AR group, but not for TD.

A doença de Parkinson (DP) é caracterizada por diferentes subtipos motores e supõe-se que o desempenho dos componentes da capacidade física é influenciado por esses subtipos. O objetivo desse estudo foi investigar o impacto que a severidade e o subtipo da DP podem trazer sobre o desempenho dos componentes da capacidade física. Trinta e seis pacientes com DP foram distribuídos em quarto grupos: com dominância de tremor (TD) inicial e TD intermediário ou acinesia (AR) inicial e AR intermediário. A força, equilíbrio, coordenação, mobilidade e capacidade aeróbia foram avaliados. AR apresentou um pior desempenho que TD em nos testes. Esse desempenho foi pior com o aumento da severidade da doença em AR, mas não em TD. Conclui-se que os grupos AR e TD são diferentes em relação ao desempenho dos componentes da capacidade física, mas principalmente, esse desempenho piora com o avanço da doença em AR, mas não em TD.
Agravo da doença de Parkinson e subtipo motor influencia componentes da capacidade física
Empeoramiento de la enfermedad de Parkinson y componentes de subtipo motor influencia la condición física
Keywords: physical capacity; Parkinson's disease; motor subtype; disease stage